Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/jp4065517
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of CH4Activation on a Monomeric Zn2+-Ion Exchanged in MFI-Type Zeolite with a Specific Al Arrangement: Similarity to the Activation Site for H2

Abstract: In this work, we used both experimental and density functional theory (DFT) calculation methods to examine the mechanism of CH 4 activation taking place on the Zn 2+ ion exchanged MFI-type zeolite (ZnMFI). The heterolytic dissociation of CH 4 on ZnMFI around 300 K was observed experimentally, causing the appearance of IR bands at 3615, 2930, and 2892 cm −1 . The first band can be assigned to the OH stretching vibration associated with the formation of the Brønsted acid site and the latter to the C−H stretching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 56 publications
8
56
0
Order By: Relevance
“…Neither FER or MOR frameworks, modified with zinc, have been previously reported to activate methane. Zn/CH 4 /ZSM‐5‐IE, prepared by aqueous ion exchange (IE) of Zn 2+ ions, also is able to activate methane, as demonstrated by the 13 C NMR signal observed at −19 ppm (Figure b), in line with observations reported by other groups . It should be noted that the conditions required to observe C−H activation of methane with the IE sample (Zn/CH 4 /ZSM‐5‐IE) were based on those reported in the literature but are substantially different to those required using samples prepared by CVD with zinc vapour.…”
Section: Resultssupporting
confidence: 83%
“…Neither FER or MOR frameworks, modified with zinc, have been previously reported to activate methane. Zn/CH 4 /ZSM‐5‐IE, prepared by aqueous ion exchange (IE) of Zn 2+ ions, also is able to activate methane, as demonstrated by the 13 C NMR signal observed at −19 ppm (Figure b), in line with observations reported by other groups . It should be noted that the conditions required to observe C−H activation of methane with the IE sample (Zn/CH 4 /ZSM‐5‐IE) were based on those reported in the literature but are substantially different to those required using samples prepared by CVD with zinc vapour.…”
Section: Resultssupporting
confidence: 83%
“…Rh 1 O 5 species on MFI zeolite promoted methane partial oxidation . In addition those, it has been reported that metal species on zeolite (mainly MFI) had quite unique activities for methane‐related reactions, i. e., aromatization of methane, combustion of methane, selective catalytic reduction of NOx with methane, and methane activation at low temperature . Therefore, metal species supported on zeolite (or MFI zeolite) possibly have the ability for methane activation.…”
Section: Introductionsupporting
confidence: 57%
“…[12][13][14] The final number shown in the sample notation indicates the ion exchange capacity that was evaluated by assuming one Zn 2+ -ion exchange per two protons in MFI.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our studies confirmed that this B3LYP-optimized MFI zeolite model comprised of 10-MR in cavities reproduced well the experimentally observed data. [12][13][14]22,[24][25][26][27][28][29][30][31] Taking our previous studies into consideration, we used the M7 site for the Al substitution position; 32 and we defined the Al configuration as the [M7-S2] arrangement. [12][13][14]30 To optimize fully the larger MFI geometry with a 10-MR cavity, we used the 6-311G(d) basis set for the zinc atom and the 6-31G (d) basis set for the Al atom, as well as four O atoms that were connected to the substituted Al atom.…”
Section: Computational Methodology (Calculation Method)mentioning
confidence: 99%
See 1 more Smart Citation